2001
DOI: 10.1001/archsurg.136.10.1150
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Unanticipated Admissions After Ambulatory Laparoscopic Cholecystectomy

Abstract: Analysis of the causes of unanticipated admission after ambulatory laparoscopic cholecystectomy may permit the identification of predictive clinical factors for postoperative admission.Design: Univariate and multivariate analyses of clinical variables associated with unplanned admission in a retrospective case-control series of ambulatory laparoscopic cholecystectomies.Setting: A major university-affiliated teaching hospital.Patients: Seven hundred thirty-one consecutive patients who underwent ambulatory lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 21 publications
6
71
0
5
Order By: Relevance
“…Operating time was in the present study found to be the only significant predictor for unexpected admission, which has been found also in at least one other study [9]. Details about circumstances that…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Operating time was in the present study found to be the only significant predictor for unexpected admission, which has been found also in at least one other study [9]. Details about circumstances that…”
Section: Discussionsupporting
confidence: 88%
“…However, some patients scheduled for outpatient LC will experience an unanticipated admission to a hospital ward after the procedure or will be re-admitted to the hospital during the early postoperative period. More studies have tried to identify factors influencing this problem including conversion to OC, operating time, intraoperative placement of a suction drain, excessive postoperative pain, urine retention, nausea/ vomiting, haematoma, infection, acute pancreatitis etc [6][7][8][9]. The aim of this retrospective study was to identify the reasons for unexpected admission as well as re-admission for patients who underwent LC as an outpatient procedure.…”
Section: Introductionmentioning
confidence: 99%
“…A readmission rate of 1.8% for our patients is in accordance to that (2%) reported in several studies. [26,27] Postoperative nausea and vomiting (PNOV) are the leading postoperative complications in cases of DSLC, several randomised controlled studies reported its occurrence yet there is no fixed nor specific pre-anesthetic drug regimens to treat such symptoms [28] Postoperative nausea and vomiting with DSLC surgery is responsible for about 0.1 -0.2% of unanticipated admissions [29] . In our study, few patients suffered from PONV that is why we report a 97% success rate of day surgery cases discharge Postoperative pain prolonged hospital stays in the ambulatory setting [30].…”
Section: Discussionmentioning
confidence: 99%
“…In more complex procedures such as laparoscopic cholecystectomy, the rate is higher and varies between 3.4% to 39%. 99,100 This variability is attributable to case selection, and surgical expertise. The main risk factors are surgical time greater than 60 min (fourfold increased risk of admission), age > 50 yr, ASA physical status class III, and surgery undertaken after 1300 hr.…”
Section: Unanticipated Hospital Admissionmentioning
confidence: 99%
“…The main risk factors are surgical time greater than 60 min (fourfold increased risk of admission), age > 50 yr, ASA physical status class III, and surgery undertaken after 1300 hr. 99,101 Other complex procedures are ENT surgery. A recent study showed that septoplasty is associated with a high risk for admission (13.4%).…”
Section: Unanticipated Hospital Admissionmentioning
confidence: 99%